Individual differences in texture preferences among European children: Development and validation of the Child Food Texture Preference Questionnaire (CFTPQ). (March 2020) - Laureati, M.; Sandvik, P.; L. Almli, V.; Sandell, M.; Zeinstra, G.G.; Methven, L.; Wallner, M.; Jilani, H.; Alfaro, B.; Proserpio, C.
Highlights: We developed a child-friendly tool to explore individual differences in texture preferences. The tool was child-friendly, culturally appropriate and had high test-retest reliability. The tool identified country-related differences. The tool identified segments of children with different texture preferences (hard- vs. soft-likers). Hard-likers were less neophobic and consumed more healthy food than soft-likers. Abstract: Texture has an important role in children's acceptance and rejection of food. However, little is known about individual differences in texture preference. The aim of this study was to develop and validate a child-friendly tool to explore individual differences in texture preferences in school-aged children from six European countries (Austria, Finland, Italy, Spain, Sweden and United Kingdom). Six hundred and ten children aged 9–12 years and their parents participated in a cross-sectional study. Children completed the Child Food Texture Preference Questionnaire (CFTPQ) and a Food Neophobia Scale (FNS). The CFTPQ consisted in asking children to choose the preferred item within 17 pairs of pictures of food varying in texture (hard vs. soft or smooth vs. lumpy). Children also evaluated all food items for familiarity. Parents completed the CFTPQ regarding their preferred items, a food frequency questionnaire for their child, and provided background information. For a subset of children, a re-test was done for the CFTPQ and FNS to assess reliability. The results showed that the tool was child-friendly, had high test-retest reliability, and identified country-related differences as well as segments of children with different texture preferences (hard- vs. soft-likers). These segments differed in consumption frequency of healthy foods, and in food neophobia.